Assessing the win–win situation of forage production and soil organic carbon through a short-term active restoration strategy in alpine grasslands - Wang, Yan; Wang, Zhicheng; Kang, Yukun; Zhang, Zhiming; Bao, Duanhong; Sun, Xiaomei; Su, Junhu (Frontiers in Plant Science, 2024)
Grassland degradation has seriously affected the ecological environment and human livelihood. To abate these, implementing effective management strategies to restore and improve the service functions and productivity of degraded grasslands is crucial. To evaluate the influences of restoration measures combined with different grazing intensities on short-term (one year) grassland restoration, the changes in soil physicochemical properties, as well as plant traits under restoration measures of different grazing intensities, reseeding, and fertilization, were analyzed. Soil organic carbon (SOC) increased to varying degrees, whereas available nutrients decreased under all combined restoration measures. Reseeding, alone and in combination with fertilization, substantially increased SOC, improved grassland vegetation status, and enhanced grassland productivity. The aboveground biomass of Gramineae and the total aboveground biomass increased under the combined restoration measures of transferring livestock out of the pasture 45 d in advance, reseeding, and fertilization (T4). Redundancy analysis revealed a strong correlation between grassland vegetation characteristics, SOC, and available potassium. Considering soil and vegetation factors, the short-term results suggested that the combination measures in T4 had the most marked positive impact on grassland restoration. These findings offer valuable theoretical insights for the ecological restoration of degraded grasslands in alpine regions.